Efficacy and safety of vorolanib plus everolimus in metastatic renal cell carcinoma: A three-arm, randomised, double-blind, multicentre phase III study (CONCEPT). (January 2023) - Sheng, Xinan; Ye, Dingwei; Zhou, Aiping; Yao, Xin; Luo, Hong; He, Zhisong; Wang, Zengjun; Zhao, Yingchao; Ji, Zhigang; Zou, Qing; He, Chaohong; Guo, Jianming; et al.
Abstract: Background: Vorolanib is a highly potent tyrosine kinase inhibitor (TKI) targeting vascular endothelial growth factor receptor (VEGFR) and platelet-derived growth factor receptor. This three-arm, randomised, registered study aimed to assess the combination of vorolanib and everolimus or vorolanib alone versus a control arm of everolimus as second-line treatment in patients with metastatic renal cell carcinoma (RCC). Patients and methods: Patients with advanced or metastatic RCC who had received one prior VEGFR-TKI were randomised (1:1:1) to receive the combination of vorolanib and everolimus or either monotherapy. Patients with brain metastases were excluded. The primary end-point was progression-free survival (PFS) assessed by the independent review committee per Response Evaluation Criteria in Solid Tumours v1.1. Results: Between 10th March 2017 and 30th May 2019, 399 patients (133 in each group) were enrolled. By the cutoff date (30th April 2020), a significant improvement in PFS was detected in the combination group compared with the everolimus group (10.0 versus 6.4 months; hazard ratio, 0.70; P  = 0.0171). PFS was similar between the vorolanib group and the everolimus group (median: 6.4 versus 6.4 months; hazard ratio, 0.94; P  = 0.6856). A significantly higher objective response rate was observed in the combination group than in the everolimus group (24.8% versus 8.3%; P  = 0.0003), whereas there was no significant difference between the vorolanib group and the everolimus group (10.5% versus 8.3%; P  = 0.5278). The overall survival data were immature. A total of 96 (72.2%), 52 (39.1%) and 71 (53.4%) grade 3 or higher treatment-related adverse events occurred in the combination group, vorolanib group and everolimus group, respectively. Conclusions: The addition of vorolanib to everolimus as 2nd-line treatment for patients with advanced or metastatic RCC who have experienced cancer progression after VEGFR-TKI therapy provided a better objective response rate and PFS than everolimus alone with a manageable safety profile. Trial registration: ClinicalTrials.gov, NCT03095040 ; Chinadrugtrials, CTR20160987. Highlights: The combination of vorolanib and everolimus showed promising efficacy. Vorolanib plus everolimus was well-tolerated with manageable safety profile. This study provided a new option for previously treated patients with metastatic renal cell carcinoma.